REPRESENTASI CITRA PEREMPUAN SEMPURNA DALAM FILM IMPERFECT (Analisis Semiotika Roland Barthes) - Sabrina Gasella Ghaisani (2023)
Imperfect: Career, Cinta & Timbangan is an Indonesian romantic drama film directed by Ernest Prakasa and produced by Kharisma Starvision Plus which premiered on Netflix on 9 July 2020. This film tells about the main character Rara who experiences body shaming from childhood until she grows up and building images of women in Indonesia that are very contradictory. This study aims to discuss the depiction of the image of a perfect woman in a film which will later be analyzed using Roland Bathes' semiotic theory in the search for denotative, connotative, and mythical meanings. The research results obtained in this study are the meanings generated from the stages in Roland Barthes' Semiotics analysis related to the representation of the perfect woman's image in the film Imperfect showing that women who have the perfect woman's image are women who are white, tall, and slim. In Indonesia, the image of the perfect woman is often an issue for every woman, and makes women always feel less than themselves. This is illustrated in the three stages of Roland Barthes' semiotics, namely the meaning of denotation, connotation, and myth.